Functioning of corn oil in frying processes - Jorge, Neuza (2004)
The objective of this study was to evaluate the functioning of corn oil during discontinuous frying processes in order to determine physical-chemical alterations. Sliced potatoes were fried establishing a device surface/ oil volume ratio (S/V) of 0.5 and 1.0 cm-1 , at 180oC, and at diverse lengths of frying time. Fifteen frying processes were conducted for each surface/volume ratio, with intervals of 30 min among them, for total period of time of 7.5 hours, and collecting oil samples after every process. In order to evaluate the oil degradation the following analytical determinations were used in duplicate: free fatty acids (%, expressed in oleic acid), peroxide value (meq/kg), refraction value (under 40oC), iodine index (g I2/100g), and total polar compounds (%). The results obtained from these analytical determinations were submitted to analysis of variance using a factorial scheme, in completely randomized statistical design , and the Tukey test. The free fatty acids increased proportionally with the length of frying time, evidencing the development of hydrolytic reactions for both surface/volume ratios. Nevertheless, the maximum values of 0.28% and 0.39% , for 0.5 and 1.0 cm-1,  espectively have not exceeded the limits established by internationalrules. The results obtained for the peroxide índex...